Growth rate, lipid content and fatty acid profiles of marine and freshwater diatoms in Malaysia - Landelsi Elfituri, Abdulfattah Mohamed (2018)
Diatoms are photosynthetic organisms that can produce lipids in large amounts and within short periods of time, and these can be processed into both biofuels and other useful commercial products. Due to this reason, diatoms are considered as a potential source of renewable energy; and one of the most important decisions in obtaining oil from microalgae is the choice of species. The current study focuses on six species of marine and freshwater diatoms, in terms of their growth rates, lipid, protein, carbohydrate and fatty acid contents. Freshwater diatoms (Sellaphora sp., Nitzschia palea, Craticula cuspidata) were isolated from Kajang pond, Selangor, Malaysia and marine diatoms (Nitzschia sigma, Nitzschia sp. and Chaetoceros calcitrans) from coastal area of Pangkor, Perak, Malaysia. Diatoms were identified by electron microscope and 18s rDNA. Among the diatom species studied, C. calcitrans, Nitzschia sp. and N. sigma (marine diatom) had significantly higher (p < 0.05) specific growth rate with 0.55, 0.51 and 0.33 (μ day-1) respectively, while freshwater diatoms (Sellaphora sp., N. palea, C. cuspidata) grew slower with specific growth rates 0.14, 0.22 and 0.25 (μ day-1). In addition, biomass of marine diatoms was (220,223 and 263 mg/L) higher than freshwater diatoms (90, 113 and 127 mg/L DW). Furthermore, the result of total lipid showed a significant difference (p < 0.05) between the mean values of marine and freshwater species. The marine diatoms species had higher lipid content (18.7 to 28 % DW) than freshwater diatoms (13 to 16 % DW). Nitzschia sp. had the highest lipid content, while C. cuspidata had the lowest lipid content. Also fatty acid showed significant difference (p < 0.05) in omega-3 (PUFAn-3). Where, marine diatoms had higher yield of Omega-3 than freshwater diatoms. On the other hand, total protein and carbohydrate were similar (p > 0.05) in diatoms, except Nitzschia sp. and C. cuspidata showed significant difference (p < 0.05) in total protein, and carbohydrate.Overall, in respects of growth rate, biomass, total lipid content and quality of fatty acid, Nitzschia sp. (marine diatom) in current study performed better than other species which makes it a good source for lipid (28% DW), protein (32% DW) and omega-3 (21.77 mg/g DW) and can use it as food in aquaculture and as source of biofuels.